Relationship between Knowledge Level and Community Compliance Receiving Covid-19 Vaccine in RT III Binanga Environment, Mamuju Regency in 2021 - Yuliana; Safriadi Darmansyah (International Journal Of Health Science, 2022)
Knowledge is the result of knowing, and this happens after people sense a certain object. Sensing occurs through the human senses, namely the senses of sight, hearing, smell, taste, and touch. Most of human knowledge is obtained through the eyes and ears. Vaccines are one of the most effective and economical ways to prevent infectious diseases, making the development of vaccines to attenuate coronavirus infections very necessary. The purpose of this study was to determine the level of knowledge with community compliance in receiving the COVID-19 vaccine. This type of research uses analytic observational, with a cross-sectional design. A sample of 115 people used the accidental sampling technique, in which the researcher used an instrument in the form of an online questionnaire via a google form and distributed via whatsapp, instagram, and zendly applications to the community in RT-III Binanga environment. The results of the study using the Chi-Squar test showed a p-value = 0.027, which means that there is a relationship between the level of knowledge and community compliance in receiving the COVID-19 vaccine.